The Place and The Role of Financial Monitoring in Anti-Money Laundering System - Maryna S. Utkina; Olha S Bondarenko; Oleg M. Reznik (Eduvest - Journal of Universal Studies, 2023)
Financial monitoring plays a pivotal role in the overall effectiveness of an anti-money laundering (AML) system. This article explores the place and role of financial monitoring in preventing and detecting money laundering activities. The authors highlighted the significance of effective financial monitoring in meeting regulatory compliance requirements. The definition of the role and place of financial monitoring in the fight against the legalisation of corruption proceeds are updated, considering the tasks and requirements set before Ukraine as a candidate country for the European Union and the challenges caused by the state of war. The article aims to analyse and provide an understanding of the importance of financial monitoring in the broader context of combating money laundering. The authors used different methods and approaches depending on the nature of the research, such as literature review, legal and doctrinal analysis, and comparative analysisб dialectical method, method of analysis and synthesis and method of terminological analysis.  The findings of this research underscore the criticality of financial monitoring in safeguarding the integrity of the financial system and protecting economies from the harmful effects of money laundering. By understanding the place and role of financial monitoring within the broader AML framework, financial institutions, policymakers, and regulators can enhance their efforts to combat money laundering and ensure a safer and more secure economic environment.